Severe calcification of forgotten Double-J ureteral stent in a patient with undiagnosed hyperparathyroidism - Ostrowska, Magdalena; Kaczyński, Szymon; Skwara, Dominika; Grześk-Kaczyńska, Magdalena; Ostrowski , Adam; Drewa, Tomasz (Journal of Education, Health and Sport, 2022)
Background Double J stent (DJ) is widely used in urological practice in patients with renal stones. However, its application is related to the risk of incrustation. We present a case of severe calcification of forgotten DJ in a patient with previously undiagnosed hyperparathyroidism (HPT). Case presentation A 30-year-old female was admitted to the Urology Department with renal colic. An initial kidney, ureter, and bladder X-ray revealed a completely calcified DJ catheter placed twelve months earlier. Unfortunately, the patient did not show up for a follow-up visit, and stent removal was not performed. Due to the extent of the disease, the patient was qualified for multistage endoscopic treatment. Total treatment lasted six months and consisted of five urereroscopies and one hybrid procedure. Simultaneously, diagnostics of a metabolic cause of the advanced stone disease suggested primary hyperparathyroidism, confirmed during parathyroid scintigraphy. After urological treatment had been completed, parathyroidectomy was performed. During a further 7-year follow-up, only one episode of renal colic occurred within the first year after treatment. The patient is stone-free until the present day. Conclusions Stents are designed to last usually up to six months, but they should be removed as quickly as possible after finishing treatment. Also, other causes such as a metabolic or hormonal imbalance should be considered. In our patient combination of forgotten DJ and HPT was the reason for excessive stone formation. Selective removal of the parathyroid gland was effective in the presented patient, with no stone recurrence observed.